Addressing Future Changes in Communication Using Hypothetical Scenarios With People With Primary Progressive Aphasia and Care Partners: A Conversation Analytic Study. - Ingvild, Winsnes; Mia, Halvorsen; Elise, Krogh; Anna, Volkmer (International Journal of Language & Communication Disorders (John Wiley & Sons, Inc.))
Background: People with primary progressive aphasia (PPA) will experience a decline in language and cognitive function, and behavioural changes are not uncommon. Decline in everyday skills has been reported and becomes more pronounced over time. Previous research has shown that people with PPA and their care partners (CPs) want to address future changes. Addressing future changes and future planning is highlighted in guidelines, such as the National Institute for Health and Care Excellence's (NICE) guidelines on Decision‐making and mental capacity. The Better Conversations with PPA is a manualised program, where planning for future changes is addressed. Aims: This study aimed to explore how the topic of planning for the future in Better Conversations with PPA is undertaken in conversations during the treatment sessions. Methods: Conversation analysis (CA) is highlighted as the "gold standard" for analysing recorded healthcare communication. Using applied CA, a method to systematically study social interaction, we analysed video recordings from four dyads, comprising a person with PPA and a care partner, participating in the Better Conversations with PPA program. The sessions are led by a speech and language therapist. Outcome and results: Our analysis shows that the structure of the conversations about the future is closely aligned with the structure of the Better Conversations with PPA program session plan. The speech and language therapist creates several opportunities for the dyads to engage in conversations about the future, using hypothetical questions and scenarios, creating a conversation environment where future changes can be addressed without the dyads having to relate this to themselves. Thereby orienting to the delicacy of the topic. Conclusion: The Better Conversations with PPA program provides a promising framework for addressing future changes. The use of hypotheticals seems to be a useful strategy to promote sensitive conversations about future changes. WHAT THIS PAPER ADDS: What is already known on this subjectPrimary progressive aphasia is a degenerative disease. Addressing future changes and future planning is highlighted in guidelines, such as the National Institute for Health and Care Excellence's guidelines on Decision‐making and mental capacity. The Better Conversations with Primary Progressive Aphasia is a manualised program, where planning for future changes is addressed. However, less is known about how the topic is treated by people with primary progressive aphasia, care partners, and speech and language therapists.What this study adds to existing knowledgeUsing conversation analysis to explore the topic of future planning in the Better Conversations with Primary Progressive Aphasia program, we found that the structure of these conversations is closely aligned with the structure of the program. Hypothetical questions and scenarios seem to be particularly powerful in addressing future changes and planning for these.What are the potential or actual clinical implications of this work?The Better Conversations with Primary Progressive Aphasia might be used as a framework to address future planning. Hypotheticals seem to be a useful strategy.